The Role of Teachers in Promoting a Positive Social Environment in Elementary Schools - Nur Haizah Aopmonaim; Waode Ekadayanti; Saqjuddin; Ahmad Muhardin Hadmar (Jurnal Wawasan Sarjana, 2025)
This study examines the role of teachers in promoting a positive social environment in an elementary school setting. A positive social environment is essential for supporting students’ social and emotional development, including cooperation, communication, and mutual respect. The purpose of this study is to analyze how teachers contribute to creating a conducive social environment and to identify the supporting and inhibiting factors involved. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers, students, and the school principal. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings reveal that teachers play a significant role as social role models, implement social learning strategies such as group work and discussions, and effectively manage classroom social interactions. However, several challenges were identified, including limited time, academic-focused priorities, and lack of specific training in social and character education. Despite these constraints, the efforts made by teachers have positively impacted students’ social development, as evidenced by improved cooperation, communication, and respect among students, although not evenly distributed. In conclusion, teachers are key agents in fostering a positive social environment, and continuous support is needed to optimize their role in enhancing students’ social development.